Transcriptional Alterations in the Trigeminal Ganglia, Nucleus and Peripheral Blood Mononuclear Cells in a Rat Orofacial Pain Model - Aczél, Timea; Kun, József; Szőke, Éva; Rauch, Tibor; Junttila, Sini; Gyenesei, Attila; Bölcskei, Kata; Helyes, Zsuzsanna (Frontiers in Molecular Neuroscience, 2018)
Orofacial pain and headache disorders are among the most debilitating pain conditions. While the pathophysiological basis of these disorders may be diverse, it is generally accepted that a common mechanism behind the arising pain is the sensitization of extra- and intracranial trigeminal primary afferents. In the present study we investigated gene expression changes in the trigeminal ganglia (TRG), trigeminal nucleus caudalis (TNC) and peripheral blood mononuclear cells (PBMC) evoked by Complete Freund’s Adjuvant (CFA)-induced orofacial inflammation in rats, as a model of trigeminal sensitization. Microarray analysis revealed 512 differentially expressed genes between the ipsi- and contralateral TRG samples 7 days after CFA injection. Time-dependent expression changes of G-protein coupled receptor 39 (Gpr39), kisspeptin-1 receptor (Kiss1r), kisspeptin (Kiss1), as well as synaptic plasticity-associated Lkaaear1 (Lkr) and Neurod2 mRNA were described on the basis of qPCR results. The greatest alterations were observed on day 3 ipsilaterally, when orofacial mechanical allodynia reached its maximum. This corresponded well with patterns of neuronal (Fosb), microglia (Iba1) and astrocyte (Gfap) activation markers in both TRG and TNC, and interestingly also in PBMCs. This is the first description of up- and downregulated genes both in primary and secondary sensory neurones of the trigeminovascular system that might play important roles in neuroinflammatory activation mechanisms. We are the first to show transcriptomic alterations in the PBMCs that are similar to the neuronal changes. These results open new perspectives and initiate further investigations in the research of trigeminal pain disorders.